دراسة معايير الأداء للنقل العام بين مدينتي اللاذقية وجبلة - رستم أكرم; زعتر نور (Latakia University Journal -Engineering Sciences Series, 2018)
تعاني معظم القرى والمدن الريفية عامة, وفي محافظة اللاذقية خصوصاً, من سوء تنظيم النقل وتخديم الناس لدرجة أضحى بها التنقل يسبب معاناة كبيرة لأغلب المواطنين، حيث تبين لنا بعد الاستقصاء عن واقع النقل بين مدينة جبلة واللاذقية، أن هذه المدينة تعاني من مشاكل النقل كغيرها من المدن، وذلك لسوء التسيير والتنظيم الذي يسود قطاع النقل في التوقيت وأعداد وسائل النقل المتاحة وقصورها في تلبية الطلب, مما يتسبب في انحدار جودة الخدمة نتيجة الازدحام والتأخير والكلفة المعنوية . قدم البحث طريقة شاملة لتقييم أداء النقل العام على المحور من خلال معايير زمن الرحلة و سرعة الرحلة، بالإضافة إلى تواتر الباصات وسعتها والحجم اليومي للركاب المنقولين, واعتبار هذه المؤشرات كمعيار لتقييم أداء النقل العام, بغية تحديد أكثر العوامل التي تؤثر على نوعية أداء النقل العام, والعمل مستقبلاً على تحسين هذا الأداء, قمنا بإجراء الدراسة الحقلية والعملية للبحث والتي تشمل اختيار مواقع الدراسة, تجميع البيانات الهندسية والمرورية اللازمة لإنجاز البحث, تصميم الاستبيانات وتوزيعها على عينات عشوائية من الركاب والسائقين العاملين على محور اللاذقية – جبلة لمعرفة آرائهم وتقييمهم لوضع النقل العام على المحور المذكور, ومن ثم قمنا بتفريغ البيانات باستخدام البرنامج الإحصائي SPSS Statistics Base وتحليل النتائج . توصل البحث إلى أن أداء النقل العام على محور جبلة - اللاذقية يعتبر ضعيفاً بشكل عام, وأن النسبة الأكبر من الركاب تعتمد في تنقلاتها على الميكروباصات, والتي لا تؤمن عملية النقل بالمستوى المطلوب. لذا وضعت مجموعة من الحلول وفقاً للظروف المحلية والتي سوف تخفف من أعباء التنقل وترفع مستوى أداء النقل . Most of the villages and rural towns, in general, and in Latakia, in particular, suffer from poor transport organizing and Serving of people so that travelling has become a great suffering for most people. After studying the transport situation between Jableh and Latakia, we found that this city suffers from transport problems like other cities. This is because of transport poor management and regulation including timing, the number of vehicles available and inability to meet demand, which causes a deterioration in service quality. The research provided a comprehensive method to evaluate the performance of public transport on the road by evaluating travel time, the journey speed, and the buses volume and frequency. Considering these indicators as a criterion for evaluating the performance of public transport to determine the most effective factors regarding the quality of performance of public transport and improve this performance in future. A field and practical study of the research has been conducted, which includes selecting of study sites, collecting engineering and traffic data, designing of questionnaires and distributing them on random passengers and drivers working on Jableh - Lattakia transportation road to find out their opinions. Then the data has been inserted into SPSS Statistics Base program for analyzing the results. The research has concluded that the performance of public transport between Jableh and Latakia is generally weak, and the largest proportion of passengers depend on their mobility on minibuses, which does not satisfy the required transportation level. Therefore, a range of solutions has been developed depending on local conditions which will ease the burden of mobility and raise the transportation performance level.